Mastering ROS for robotics programming design, build, and simulate complex robots using Robot Operating System and master its out-of-the-box functionalities - Joseph, Lentin (Community experience distilled, 2015)
Chapter 2: Working with 3D Robot Modeling in ROS; ROS packages for robot modeling; Understanding robot modeling using URDF; Creating the ROS package for the robot description; Creating our first URDF model; Explaining the URDF file; Visualizing the robot 3D model in Rviz; Interacting with pan and tilt joints; Adding physical and collision properties to a URDF model; Understanding robot modeling using xacro; Using properties; Using the math expression; Using macros; Conversion of xacro to URDF; Creating the robot description for a seven DOF robot manipulator; Arm specification.